ROLE OF VITAMIN C AND E ON GENOTOXICITY, HEMATOLOGICAL AND BIOCHEMICAL INVESTIGATION IN CYPRINUS CARPIO L. FOLLOWING ZINC OXIDE NANOPARTICLES EXPOSURE - H. H. Faik,; S.A. Mustafa, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to evaluate the role of vitamins C and E on genotoxicity, biochemical and hematological indices in common carp, Cyprinus carpio following zinc oxide nanoparticles exposure. Zinc oxide nanoparticles were synthesized (size was < 34nm) and characterized using Fourier Transform Infrared Spectra (FTIR) and X-Ray Diffraction (XRD) analysis. About 120 common carp (weight 20.0-32.0 g) were randomly divided into 12 tanks at rate of 10 fish/tank (two (replicates/treatment); fish were fed diet as follows: Control (C) were fed basal diet; T1 fish were fed basal diet mixed with vitamins C and E (400 mg/kg); T2 and T3 fish were fed basal diet mixed with 10%and 15% ZnONPs respectively; T4 and T5  fish were fed basal diet mixed with ZnONPs 10% and 15% plus vitamins C and E (400 mg/kg dw) respectively. Post 40 d feeding trail, variable changes were registered in blood indices (“Hb content, PCV%, WBCs and RBCs numbers”) in all treated groups compared to C and T1 groups. The highest DNA damage (% tail DNA using Comet assay) was seen in T2 and T3 which asserted highly significant increased (P≤0.01) compared to C and to treated groups. As well as, glutathione peroxidase (GPx) activity exhibited highly significant increase (P≤0.01) in T2 and T3 groups relative to C, T4, T1, T5 respectively. This investigation clearly proved that sub-lethal doses (10 and 15% in diet) of ZnONPs were able to induce an oxidative stress in carp fish as reflected by significantly increase of DNA damage to erythrocytes and “the combination of vitamins C and E was able to alleviate the oxidative stress generated due to exposure to ZnONPs.”